(untitled) (Caligrama: Revista de Estudos Românicos, 2025)
In this paper, I propose an extension of the joint attention scenes models to include mediated multimodal communicative settings. From this extension, I discuss how the FrameNet analytical model can be used for the annotation of multimodal genres so as to include categories capable of accounting for invited shifts in joint attention in visual narratives. I revisit the literature on deixis and claim that, despite the fact that much of the foundational research on this topic proposes correlations between deixis in verbal language and other semiotic modes, the focus of research lies on the linguistic material in which the expression of deixis is grounded. By bringing together contributions from human communication studies, from the analysis of deixis in narratives and from Frame Semantics, I claim that semiotic devices of different types can be mobilized in filmic narratives to invite viewers to promote shifts in the center of the joint attention scene. To illustrate the proposed typology, I provide example analyses of deictic center shifts in films and describe the annotation methodology incorporated to the FrameNet model to account for them.